Adaptive Management of Renewable Resources - Walters, C. J. (Macmillan Publishers Ltd, 1986)
The author challenges the traditional approach to dealing with uncerta inty in the management of such renewable resources as fish and wildlif e. He argues that scientific understanding will come from the experien ce of management as an ongoing, adaptive, and experimental process, ra ther than through basic research or the development of ecological theo ry. The opening chapters review approaches to formulating management o bjectives as well as models for understanding how policy choices affec t the attainment of these objectives. Subsequent chapters present vari ous statistical methods for understanding the dynamics of uncertainty in managed fish and wildlife populations and for seeking optimum harve st policies in the face of uncertainty. The book concludes with a look at prospects for adaptive management of complex systems, emphasizing such human factors involved in decision making as risk aversion and co nflicting objectives as well as biophysical factors. Throughout the te xt dynamic models and Bayesian statistical theory are used as tools fo r understanding the behavior of managed systems. These tools are illus trated with simple graphs and plots of data from representative cases. This text/reference will serve researchers, graduate students, and re source managers who formulate harvest policies and study the dynamics of harvest populations, as well as analysts (modelers, statisticians, and stock assessment experts) who are concerned with the practice of p olicy design.